2018
DOI: 10.1021/acs.joc.8b01642
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-Controlled Regio- and Stereoselective Synthesis of (Z)- and (E)-N-Styrylated Carbazoles, Aza-carbazoles, and γ-Carbolines via Hydroamination of Alkynes

Abstract: We report herein the substrate-controlled regio- and stereoselective hydroamination of carbazoles, aza-carbazoles, and γ-carbolines with functionalized aromatic as well as aliphatic alkynes in a KOH/DMSO system in good yields. The electronic effect of the substrates governs the stereochemistry of the product. Electron-donating alkynes provided ( Z)-stereoselective products, and electron-withdrawing alkynes provided ( E)-stereoselective products. This approach also provides an easy route for the synthesis of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 53 publications
0
7
1
Order By: Relevance
“…This observation is also in line with the results of the solvent screen, which revealed that polar, coordinating solvents have a detrimental effect on the product yield. In contrast to previous reports on Cu­(I)-catalyzed high-temperature hydroamination reactions of pyrrole, we could observe the selective formation of the exo- addition product …”
contrasting
confidence: 99%
See 1 more Smart Citation
“…This observation is also in line with the results of the solvent screen, which revealed that polar, coordinating solvents have a detrimental effect on the product yield. In contrast to previous reports on Cu­(I)-catalyzed high-temperature hydroamination reactions of pyrrole, we could observe the selective formation of the exo- addition product …”
contrasting
confidence: 99%
“…Based on our interest in the functionalization of N -heterocycles via carbene intermediates, we hypothesized that the hydroamination of carbazole heterocycles with alkynes should provide an elegant entry into N -vinyl-substituted carbazoles (Scheme b). N -Vinyl carbazoles are important building blocks in the synthesis of carbazole-based electroluminescent materials, and currently available synthesis methods involve cross-coupling of vinyl bromides, oxidative coupling of olefins, addition reactions under strongly basic conditions, or carbene transfer of tosylhydrazones (Scheme b) . The direct synthesis of vinyl carbazoles from readily available starting materials at ambient conditions thus remains a challenge in organic synthesis, and the development of a hydroamination reaction of alkynes with unprotected carbazole would open up an direct approach toward this important structural element (Scheme c).…”
mentioning
confidence: 99%
“…37 In addition, novel approaches from both traditional and modern chemistry continue to emerge. [40][41][42][43][44] However, it is still a challenge to offer novel synthetic methods that provide functionalized g-carbolines from readily available precursors.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Wang and co‐workers have developed a trideuteromethylating reagent TDMSOI which incorporates −CD 3 group into aromatic functionalities [23] . The research work of our group is primarily accented to the superbase‐mediated nucleophilic addition reactions in a step‐economical way [24–26] . In continuation of our ongoing work with alkynes and super‐base; in this work, we have described the selective deuteration of terminal alkyne using inexpensive KOH/DMSO‐d 6 with a high level of heavy hydrogen incorporation (Scheme 1vi).…”
Section: Figurementioning
confidence: 98%